2017
DOI: 10.3390/app7100982
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stress and Deformation Analysis in Butt Welding on 6 mm SUS304 Steel with Jig Constraints Using Gas Metal Arc Welding

Abstract: This article proposes a novel method for analyzing residual stress and deformation in butt welding on 6 mm SUS304 stainless steel plates, using MSC.MARC, a commercial finite element method software, to find the best location for jig fixtures that will minimize welding deformation. Simulation and experimental studies show that a distance of 100 mm between the jig center and the welding bead center is best for inhibiting welding deformation when the jigs experience downward displacement at 0 mm on the steel plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Costa et al 14 compared the welding-induced residual stresses of the cold-wire and conventional MAG welding processes by using X-ray diffraction and acoustic birefringence in their experimental study. Kung et al 15 proposed a novel method for analyzing residual stresses and deformations in butt-welded thin stainless plates using a numerical method to find the best location for jig fixtures that would minimize welding deformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Costa et al 14 compared the welding-induced residual stresses of the cold-wire and conventional MAG welding processes by using X-ray diffraction and acoustic birefringence in their experimental study. Kung et al 15 proposed a novel method for analyzing residual stresses and deformations in butt-welded thin stainless plates using a numerical method to find the best location for jig fixtures that would minimize welding deformation.…”
Section: Discussionmentioning
confidence: 99%
“…Costa et al compared the welding‐induced residual stresses of the cold‐wire and conventional MAG welding processes by using X‐ray diffraction and acoustic birefringence in their experimental study. Kung et al proposed a novel method for analyzing residual stresses and deformations in butt‐welded thin stainless plates using a numerical method to find the best location for jig fixtures that would minimize welding deformation. Adamczuk et al experimentally analyzed the angular distortions in multipass welded thick steel plates using four different heat inputs that varied between 0.6 and 2.5 KJ/mm, and they proposed appropriate analytical solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reduced usage of temporary piece, while maintaining a welding quality of hull block, is required. Interest in the optimization of butt joint welding has generated many analytical and experimental studies [3][4][5][6]. Furthermore, the studies have been made to reduce residual stresses and deformations of fillet weld joints.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efforts to precisely evaluate the residual stress and deformation of the butt-welded joint have been aided by finite element analysis, thanks to the development of increasingly more powerful computers. However, most of the research done has Interest in the optimization of butt joint welding has generated many analytical and experimental studies [3][4][5][6]. Furthermore, the studies have been made to reduce residual stresses and deformations of fillet weld joints.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [14] verified the deformation reduction according to the jig constraint position and pitch through experiments and theoretical analysis, and they addressed longitudinal and transverse shrinkage as well as angular distortion, which were significantly reduced. Kung et al [15] showed the deformation of SUS304 steel according to the number of jigs using finite element analysis and proposed the optimal location of jig fixtures. Park et al [16] derived the constraint coefficient through various welding experiments and analyses, obtaining the actual degree of constraint of a ship block and devising the optimal welding sequence.…”
Section: Introductionmentioning
confidence: 99%